PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MATERI PERSAMAAN KUADRAT DENGAN PENDEKATAN SAINTIFIK PADA SISWA KELAS IX MTS AN-NUR CIKALONGWETAN - Anita Apriliana; M. Afrilianto; Ima Saridah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study is to analyze the increase in understanding of mathematical concepts in quadratic equations. The method used is Classroom Action Research with the stages of research using the Taggart model. The subjects in this study were class IX students at MTs An-Nur Cikalongwetan with a sample of 15 students. Data collection techniques using test and non-test instruments. The test instruments used were pretest and posttest with indicators of understanding students' mathematical concepts. The non-test instrument was in the form of a questionnaire related to student learning independence. Data analysis using descriptive qualitative with tests processed using N-Gain, while the non-test is processed using a Likert scale. Based on the N-Gain analysis, it was concluded that there was an increase in students' understanding of mathematical concepts from the results of the students' pretest and posttest with a total percentage of 62.3% with quite effective criteria. Student learning independence is at an average percentage of 61.04% with strong criteria.